Using a Computer Module to Teach Use of the EpiPen® - Rai, Amandeep Singh; Glicksman, Jordan; Wong, Eric; Doyle, Phil; Fung, Kevin (Canadian Medical Education Journal, 2011)
Background: The medical literature suggests that patients and physicians are deficient in their ability to use a self-injectable epinephrine device (EpiPen®) for management of anaphylaxis. This study aims to determine whether a computer module is an effective tool for the instruction of a technical skill to medical trainees. Methods: ﻿We conducted a two group comparison study of 35 Post-Graduate Year 1 and 2 Family Medicine residents. Participants were instructed on use of the EpiPen® using either a written module or a computer module. Participants were evaluated on use of the EpiPen® using standardized objective outcome measures by a blinded assessor. Assessments took place prior to and following instruction, using the assigned learning modality. ﻿﻿﻿Results: There were 34 participants who completed the study. Both groups demonstrated significant improvement in demonstrating use of the EpiPen® following training (p <0.001 for both). A significant post-training difference favouring the computer module learners over the written module learners was observed (p = 0.035). However, only 53% and 18% of candidates (computer module and written module, respectively) were able to correctly perform all of the checklist steps. Conclusion: While our findings suggest computer modules represent an effective modality for teaching use of the EpiPen® to medical trainees, the low number of candidates who were able to perform all the checklist items regardless of modality needs to be addressed.